A MODEL OF EARLY DIAGENETIC PROCESSES FROM THE SHELF TO ABYSSAL DEPTHS - Soetaert K.; Herman P.M.J.; Middelburg J.J. (My University, 1996)
We present a numerical model of sedimentary early diagenetic processes that includes oxic and anoxic mineralization. The model belongs to the new wave of early diagenesis models that account for depth-dependent bioturbation and porosity profiles; it can be used both for calculating steady-state conditions and transient simulation. It was developed to reproduce the cycling of carbon, oxygen, and nitrogen along the ocean margin; it resolves the sediment-depth profiles of carbon, oxygen, nitrate, ammonium, and other reduced substances.Organic carbon is modeled as two degradable fractions with different first-order degradation rates and nitrogen:carbon ratios, to account for the decreasing reactivity and N ratio of the organic matter with depth into the sediment. The consumption of oxygen and nitrate as terminal electron acceptors is explicitly modeled, and mineralization is limited both by carbon (first order kinetics) and by oxidant availability (Michaelis-Menten type kinetics). Nitrification and oxic mineralization are decoupled, which allows the description of ammonium profiles. Mineralization processes using other oxidants (manganese oxides, iron oxides, sulphate) are lumped into one process, where degradation is only carbon limited; the terminal electron acceptors are not explicitly modeled, only the production of reduced substances is described. These substances are in part permanently removed (e.g., pyrite formation below the bioturbation zone) and partly diffuse towards the oxic layer where they react with oxygen.The values of several parameters were constrained using literature-derived relationships. The model was calibrated on a dataset obtained from the literature, which relates the magnitude of the different pathways to total organic carbon mineralization. The influence of carbon flux, bioturbation, sedimentation rate, bottomwater concentrations of oxygen, and nitrate and carbon degradability on the different mineralization pathways is examined. The relative contribution of the oxic mineralization in the model is significantly depressed under high organic flux, under low bottomwater oxygen conditions and when the bioturbation increases; higher carbon degradability has only a small positive effect, while sedimentation rate is relatively unimportant. Denitrification is mainly influenced by the nitrate concentration in the overlying bottomwater.